Effectiveness of periodontal therapies on the treatment of different aetiological factors in puberty - C Kara (Journal compilation 2007 Blackwell Munksgaard, 2007)
The aim of the present study was to compare oral improvement achieved by different periodontal therapies (surgical and non-surgical) for different aetiological factors induced gingival overgrowth in 60 subjects (mean age ± SD = 12.33 ± 1.05 years; age range = 12–15 years).